(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
A 50 years old non-smoker female with the history of right flank pain and hematuria surgically treated with right sided radical nephrectomy. Macroscopically it showed a large growth located at the lower pole of the right kidney. Histologically the tumor was composed of exuberant sarcomatous elements predominantly malignant fibrous histiocytoma like pattern and diagnosed as sarcomatoid renal cell carcinoma. There was no scope for immunohistological analysis of that tumor in our setup. It is important to recognize the sarcomatoid component in the renal tumors because of its aggressive behavior and adverse prognosis. We report herein a case of sarcomatoid renal cell carcinoma histomorphogically. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21039